Defining and Redefining its Role in Biology: Synthetic Biology as an Emerging Field at the Interface of Engineering and Biology - Ng, Wenfa (Archives of Clinical and Medical Case Reports, 2022)
Synthetic biology is often misunderstood as creation of artificial life or new biology using principles different from those of extant organisms around us. But, fundamentally, the field is about engineering biology in a more efficient and effective way and endowing new functions in existing organisms using a more refined and predictable approach. Thus, synthetic biology as encapsulated by the field it helps defined is enhanced recombinant DNA technology, an example of which is modular and orthogonal “standard swappable biological parts”. But, as the field grows and matures, various “allied” fields are subsumed into it such as metabolic engineering, protein engineering, directed evolution, origins of life research, and systems biology, which in totality represents a new perspective of how engineering principles can be utilized to expand, in scope and depth, the realms of questions that biology ask. Two parallel approaches, directed evolution and de novo protein design, are frequently used to engineer new phenotypes into organisms. Similar to evolution but with purposeful use of selection pressure to elicit progressive refinement of specific traits in an efficient manner, directed evolution is a powerful methodology that generates, at the cell level, libraries of mutants of slightly different function such as differing resistance to heavy metals, that upon exertion of continued selection pressure, led to the evolution of a strain capable of thriving under a hostile environment previously inhabitable to the organism. Taking a different approach, de novo protein design taps on advances in biomolecule structure modelling together with bioinformatic sequence search for inserting, in a structure defined manner, specific amino acids (natural or unnatural) in a protein structure to endow desired functionality, where one highly sought function is catalysis of unnatural reactions such as the Diels-Alder reaction. Long chain